Sharing Hidden Know-How : How Managers Solve Thorny Problems With the Knowledge Jam - Pugh, Katrina (San Francisco Jossey-Bass, 2011)
To manage business operations let alone innovate amid frequent restructurings, outsourcings and retirements, leaders must quickly capitalize on hidden know-how (knowledge). That is, know-how that lives inside their organizations or networks in the teams, processes and experts that comprise them
Include Reference, Notes and Index
Keywords: Knowledge management -- Organizational learning--Management -- Organizational learning